Hello darkness my old friend: How policy learning can contribute to value destruction. - Zaki, Bishoy L. (Policy Studies Journal, 2024)
For decades, policy learning has been often viewed as a force for the common good, a process that aims at creating value for the public through problem‐solving. While learning can indeed contribute to value creation, darkness also lurks therein, where learning can also contribute to value destruction. Yet, the dark side of policy learning remains under‐explored and under‐theorized, particularly going beyond meso‐level policy and organizational failures or "mishaps." This article draws on policy learning and value theories to conceptualize two types of policy learning failures and plot how they can contribute to the destruction of value in the public sphere: misdirected learning design failures (non‐deliberate and cybernetic) and normative failures (intentional and deontological). This is done while addressing the two key facets of value in the public sphere; public values, being the guiding principles of policymaking and governance, as well as public value, being the worth of public services delivered to the citizenry. In doing so, this contributes to the literature by addressing calls for exploring the dark side of learning, expanding our understanding of learning outcomes beyond organizational and policy level implications, and developing novel fundamental understandings of value destruction mechanisms.